FORMALISASI SYARIAT ISLAM DI INDONESIA (Prespektif Gereja Katolik) - Bolong,OCD, Bertholomeus (Al-Mawarid Jurnal Hukum Islam, 2006)
Formalization discourses on Syariat Islam in Indonesia today, has called for serious discussions from the different categories of people. And various opinions have been put forward, either pro or con. Differences in opinion are normal fact, because they do reflect not only the existence of the democracy but also the hetrogenity of the religious life in Indonesia, admitted and protected by the law and constitution. As a part of Indonesian society, Catholic people are called to give their opinion or ideas. The expression of thought is one of the realization of the freedom and tolerance of religious life in Indonesia. Kata-kata Kunci: Formalisasi, Syariaat islam, gereja katholik.